Prestige and European arbitration: about the Judgment London Steam-Ship of the CJEU (case C-700/20) - Gómez Jene, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The judgment of the CJEU accepts that, in principle, a judgment entered in terms of the award may constitute a judicial decision for the purposes of the application of Article 45.1 c/ of the Brussels I Regulation recast. However, in order to be able to effectively attain such status, the judgment must necessarily meets a series of requirements. These requirements must be appreciated in a sort of test of equivalence with respect to a “genuinely European” decision and are specified in what the CJEU has described as “two fundamental rules” of the Regulation: the relative effect of the arbitration clause and lis pendens.
Keywords: European arbitration; Regulation Brussels I recast; Arbitration clause; Arbitral award; Irreconcilable judgment; Lis pendens; Public policy